Pharmacokinetics of Direct Oral Anticoagulants in Emergency Situations: Results of the Prospective Observational RADOA-Registry - Lindhoff-Last, Edelgard; Birschmann, Ingvild; Kuhn, Joachim; Lindau, Simone; Konstantinides, Stavros; Grottke, Oliver; Nowak-Göttl, Ulrike; Lucks, Jessica; Zydek, Barbara; von Heymann, Christian; Sümnig, Ariane; Beyer-Westendorf, Jan; Schellong, Sebastian; Meybohm, Patrick; Greinacher, Andreas; Herrmann, Eva; On behalf of the RADOA-Registry Investigators (Reversal Agent use in patients treated with Direct Oral Anticoagulants or vitamin K antagonists Registry) (Thrombosis and Haemostasis, 2021)
Background Direct oral anticoagulants (DOACs) are increasingly used worldwide. Little is known so far about their pharmacokinetics in emergency situations.Methods A prospective, observational registry was performed to determine the clinical course in consecutive patients with major bleeding or urgent surgery treated with DOACs. In samples collected as part of routine care DOAC drug concentrations were measured using ultraperformance liquid chromatography-tandem mass spectrometry. Anticoagulant intensity at first presentation and drug half-life (t1/2), tested in repeat samples, were evaluated.Results A total of 140 patients were prospectively included. Pharmacokinetic data were available in 94% (132/140) of patients. Note that 67% (89/132) experienced life-threatening bleeding and 33% (43/132) needed an urgent surgery. For pharmacokinetic analysis a total of 605 blood samples was available. Median concentration on admission was 205 ng/mL for rivaroxaban and 108 ng/mL for apixaban. All treatment groups showed a high variation of drug concentrations at baseline. In rivaroxaban-treated patients t½ was 17.3 hours (95% confidence interval [CI]: 15.4–19.7) without significant difference in both groups (major bleeding: t½ 16.7 hours, 95% CI: 14.7–19.3; urgent surgery: t½ 19.7 hours, 95% CI: 15.2–27.9; p = 0.292). In apixaban-treated patients t½ was 25.0 hours (95% CI: 22.9–27.6) with a longer t½ after urgent surgery (t1/2: 30.8 hours; 95% CI: 26.9–36.4) compared with severe bleeding (t1/2: 20.8 hours; 95% CI: 18.8–23.2; p < 0.001).Conclusion Emergency patients under DOAC treatment show a high variation of anticoagulant concentrations at baseline. Compared with rivaroxaban, apixaban showed a lower median concentration on admission and a longer t½.
Keywords: direct oral anticoagulants; pharmacokinetics; emergency; major bleeding; urgent surgery